Handbook of plant biotechnology - Christou, Paul; Klee, Harry (John Wiley & Sons, 2004)
The Handbook provides extensive coverage of the field including articles on plant genetic modification; applications of plant biotechnology to crop improvement in agriculture, production systems for pharmaceutical proteins, ethics and safety issues, public perception and public relations; scale-up, and testing and legislation. Comprising 71 articles from more than 100 contributors, the online Handbook of Plant Biotechnology is an invaluable resource for researchers, scientists, graduate students or postdoctoral workers active in the fields of botany, agriculture, horticulture and food science.